2016
DOI: 10.4028/www.scientific.net/msf.879.948
|View full text |Cite
|
Sign up to set email alerts
|

Synchrotron Investigation on the Precipitation Behaviour of Niobium Microalloyed Steel

Abstract: The precipitation and dissolution behavior of niobium carbo-nitrides is of particular interest for many technical applications. Niobium-microalloyed high strength low alloy (HSLA) steels are widely used in civil construction, automobile and line pipe applications. These steels rely on thermomechanical processing. In this context, coupled processes like thin slab casting and thermomechanical rolling of microalloyed steel grades require most precise information on the precipitation state at the individual proces… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 5 publications
0
4
0
Order By: Relevance
“…In this context, it has previously been shown that with high‐energy synchrotron X‐ray scattering, the increase of precipitates when annealing above 500 °C was detectable in micro‐alloyed Nb steels with volume fractions below 0.1%. [ 7,8 ]…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this context, it has previously been shown that with high‐energy synchrotron X‐ray scattering, the increase of precipitates when annealing above 500 °C was detectable in micro‐alloyed Nb steels with volume fractions below 0.1%. [ 7,8 ]…”
Section: Introductionmentioning
confidence: 99%
“…In this context, it has previously been shown that with high-energy synchrotron X-ray scattering, the increase of precipitates when annealing above 500 °C was detectable in micro-alloyed Nb steels with volume fractions below 0.1%. [7,8] The primary objective of this work was to study precipitate development in a commercial Ti-Nb micro-alloyed steel in thermomechanically treated samples and to assess if high-energy synchrotron SAXS could be used to study mm-thick samples and to detect very small volume fractions of <10 nm sized particles. The high-energy synchrotron X-ray beamline P21.2 at DESY was used to track even minor changes of very small volume fractions of nanosized particles.…”
mentioning
confidence: 99%
“…Precipitate number densities cannot be determined via two-dimensional electron microscopy investigations on carbon extraction replicas and/or metallographically prepared cross sections of bulk samples. Further, the small volume fraction of precipitates (below 0.1%) limits the precipitate number density determination to high-resolution tomographic techniques such as X-ray diffraction in synchrotrons [22] or small-angle neutron scattering [5,23].…”
Section: Introductionmentioning
confidence: 99%
“…using EXPGUI (Toby, 2001) which is a graphical user interface for GSAS (Larson & Von Dreele, 2000) Such a non-ambient environment may for example be a halogen lamp furnace with a protective atmosphere, equipped with windows for X-rays diffraction measurements (e.g. Klinkenberg & Klein, 2016). In case of measurements in any sort of container, one of course always has to measure a reference sample in the same environment (yet usually at ambient conditions) to account for the likely attenuation effects e.g.…”
Section: -108mentioning
confidence: 99%